Discussion of 'Strategic pricing by Big 4 audit firms in private client segments'. (23rd August 2013) - Carson, Elizabeth; Cahan, Steven
Abstract This article discusses the paper by Dutillieux et al., (2013). The comments are in four main areas, regarding the importance of the research question, the setting in which the study is located, the theoretical development of the study and some thoughts regarding both supply‐ and demand‐side considerations around auditor change.